THE ROLE OF PSYCHOLOGICAL WELL-BEING IN BOOSTING IMMUNE RESPONSE: AN OPTIMAL EFFORT FOR TACKLING INFECTION - Latief, Abdurachman; Herawati, Netty (African Journal of Infectious Diseases (AJID), 2018)
Background: Many attempts have been made to improve human body resistance towards infection. These attempts were exemplified by promotion of hygiene and the use of antiseptic ingredients, pharmaceutical compounds, and vaccines. To prove an aspect which intentionally less explored was attempt to boosting the host immune responses by creating a psychological balance, which was important aspect of psychological well-being.Material and Method: These article reviews searched and compiled using database Google Scholar, from 1995 to latest. Search keywords were: immune response, psychological well-being, psychological ill-being.Results: Based on literature our findings showed that psychological well-being was proven could increase human body immune response. The evidenced were by improvements of several indicators in saliva, blood and plasma. In other way, psychological ill-being was associated with decreased immune responses. Numerous studies compiled and discussed in review also suggested that improving immune response through psychological well-being could increase living comfort.Conclusion: The psychological well-being could improve the human body immune responses, enhance resistance towards diseases (including infectious diseases), and create a spiritually and physically more prosperous life.